Tolerance for uncertainty in elderly people - Kachmaryk, Khrystyna; Grabovska, Sophia; Ostrovska, Kateryna; Syniev, Viktor (Journal of Education Culture and Society, 2020)
The aim of the study. The aim of the paper is a comparison of tolerance to uncertainty in two groups of elderly: the students of the University of the Third Age (UTA) and older people who are not enrolled but help to educate grandchildren. A relation to uncertainty was shown to infl uence on decision making strategy of elderly that indicates on importance of the researches. Methods. To obtain the objectives of the paper the following methods were used: 1) Personal change readiness survey (PCRS) adapted by Nickolay Bazhanov and Galina Bardiyer; 2) Tolerance Ambiguity Scale (TAS) adapted by Galina Soldatova; 3) Freiburg personality inventory (FPI) and 4) The questionnaire of self-relation by Vladimir Stolin and Sergej Panteleev. 40 socially involved elderly people were investigated according the above methods, 20 from UTA and 20 who are not studied and served as control group. Results. It was shown that relations of tolerance to uncertainty in the study group of students of the University of the Third Age substantially differ from relations of tolerance to uncertainty in group of older people who do not learn. The majority of students of the University of the Third Age have an inherent low tolerance for uncertainty, which is associated with an increase in expression personality traits and characteristics in self-relation. The group of the elderly who are not enrolled increasingly shows tolerance of uncertainty, focusing on  the social and trusting relationship to meet the needs of communication, and the ability to manage their own emotions and desires than a group of Third Age university students. Conclusions. The results of experimental research of the third age university student’s peculiarities of the tolerance to uncertainty were outlined. It was found that decision making in the ambiguity situations concerning social interaction is well developed in elderly who do not study. The students of the University of Third Age have greater needs in conversation, social interaction than the control group and should learn to make decisionin ambiguity or uncertainty situations.